A review of various reversible embedding mechanisms. (19th November 2021) - Natarajan, Yuvaraj; Raja, R. Arshath; Kousik, N.V.; Saravanan, M.
The ability of communicating the information and hiding secret information has gained much advancement in the field of image processing. Watermarking in the image processing hides the digital information in an unsecured medium or digital image. A digital watermark that is embedded in an image verifies the integrity of the original data/work. Thus watermarking process helps in the protection of data/work of an owner and avoids duplication of contents. The reversible watermarking gains its major importance in the sensitive areas like health, military and law. The concerns associated with reversible watermarking like error resiliency, embedding capacity and coding efficiency is considered as a major factor for surveying. The main objective is to provide an extensible survey of state-of-the-art methods in reversible watermarking on several applications in image processing domain. This paper reflects latest progress of reversible watermarking in researches and specifies the key issues to improve the work in future.